DEVELOPING PARENTHOOD AWARENESS IN YOUTH THROUGH PRENATAL PEDAGOGY - Elena Ivanovna Tolokneeva (Вестник Северо-Кавказского федерального университета, 2022)
The item offers a view on the issues related to developing parental awareness in the student youth, importance of taking into account the prenatal development of the child, increased prenatal competence in the future parents, as well as stress the significance of this phenomenon both for individuals and for the mankind at large.